NON SECULARIZATION OF MARRIAGE LEGAL PROCEDURE BASED ON BELIEF IN ONE ALMIGHTY GOD IN INDONESIA - Burhanudin Harapah; Solikhah Muslich Sugiyono; Luthfiyah Trini Hastuti (Yustisia Jurnal Hukum, 2020)
When disputing in court, non-Muslim citizens use positive laws established by the state that do not involve their religious beliefs. Philosophically, this is on the contrary to the constitution, which states that the country is based on belief in one Almighty God. Moreover, in every decision, judges are formally required to begin with "For the sake of the one Almighty God." This phenomenon may be the result of cultural and/or structural factors that require a research study. This research is normative legal research to devise models of religious legal formulation in the legal system in Indonesia. The results of the study illustrate that changing secular marriage law to religious marriage law is possible through formal procedural rules and substantial material rules. In the initial stages, efforts should be made to change the formal procedural arrangement stage using a procedure to examine, adjudicate, and decide a case. Before deciding on a divorce case, the religion of the disputing parties needs to be involved by (1) appointing a judge who is of the same religion as the disputing parties to examine, adjudicate, and decide the case; (2) requiring judges to present expert witnesses from religious leaders of the disputing parties. This is very important because religion is a truth system based on belief and not all religious beliefs can be rationalized.